2023
DOI: 10.1128/msphere.00538-22
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of the Abundance and Composition of Antibiotic Resistance Genes in Hospital Wastewater in Benin, Burkina Faso, and Finland

Abstract: The global emergence and increased spread of antibiotic resistance threaten the effectiveness of antibiotics and, thus, the health of the entire population. Therefore, understanding the resistomes in different geographical locations is crucial in the global fight against the antibiotic resistance crisis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…The presence of ESBL-producing E. coli in hospital effluents is of particular concern. In this study, all E. coli isolates from hospital effluents were found to be ESBL producers, consistent with the findings of Markkanen et al ( 21 ), who identified hospital effluents as hotspots for ESBL genes. Similarly, Gumede et al ( 37 ) reported a high number of ESBL-producing E. coli in hospital wastewater in South Africa.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of ESBL-producing E. coli in hospital effluents is of particular concern. In this study, all E. coli isolates from hospital effluents were found to be ESBL producers, consistent with the findings of Markkanen et al ( 21 ), who identified hospital effluents as hotspots for ESBL genes. Similarly, Gumede et al ( 37 ) reported a high number of ESBL-producing E. coli in hospital wastewater in South Africa.…”
Section: Discussionsupporting
confidence: 92%
“…Although studies have reported the presence of ESBL-producing bacteria and their resistance genes in various samples from Africa and globally ( 7 , 20–23 ), limited data exist on the prevalence of ESBL-producing Enterobacterales in healthy pregnant women, the food chain, and the environment in Benin ( 21 , 24–28 ). Therefore, the present study investigates the prevalence and characteristics of ESBL-producing E. coli in healthy pregnant women, the hospital environment, and the food chain within various tertiary hospitals in Benin.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of fluoroquinolone genes in the category varied between 7.2% and 80.3%, where the qnrB-31 genes were found to have the highest frequencies. Markkanen et al ( 2022 ) discovered the carbapenemase genes blaKPC, blaNDM, blaIMP, blaOXA-48, and blaOXA-58 in hospital wastewater samples from Burkina Faso and Finland. It was believed that Acinetobacter baumannii , an opportunistic pathogen is known to cause nosocomial infections, was almost exclusively associated with the blaOXA-58, blaOXA-51, and blaOXA-23ARGgenes (Cacace et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“… (6) Brucella spp. (18) Burkina- Faso 2015 Wastewater used for urban agriculture Comamonadaceae, Chroococcaceae, Streptococcaceae, Enterobacteriaceae, Enterococcaceae, Staphylococcaceae NA bla OXA-226 , bla OXA-256 , bla OXA-347 , bla OXA-46 , bla SHV-100 , bla GES-21 , bla OXA-256 , (multiple virulence genes) NA [ 54 ] 2019 Hospital Wastewater A. baumannii NA bla OXA-58 , bla OXA-46 , bla CMY-2 , bla OXA-101 , bla OXA-56 , bla OXA-397 , bla OXA-48 , bla IMP , bla NDM , bla VIM , bla GES NA [ 50 ] 2019–2021 Wastewater from healthcare centers E. coli 35/107 (32.71) NDM, OXA-48 NA [ 55 ] K. pneumoniae 11/60 (18.33) Chad 2016–2018 Household meals, fresh milk, fresh meat, fresh fish, fresh vegetables E. coli, S. aureus 6/48 (12.5) NA NA [ 56 ] NA Fresh vegetables and fruits E. coli, S. aureus 6/60 (10) NA NA …”
Section: Resultsmentioning
confidence: 99%